Tenecteplase is here: navigating the shift of a stroke thrombolytic in the United States prior to FDA approval: a mini-review on rationale, barriers, and pathways - Burwell, Julian M.; Howay, Jason R.; Wasko, Lisa; Doucoure, Samantha; Kerestes, Jamie L.; Schirmer, Clemens M.; Ermak, David; Noto, Anthony; Hendrix, Philipp (Frontiers in Neurology, 2025)
The transition from alteplase (TPA) to tenecteplase (TNK) in acute ischemic stroke (AIS) management is gaining traction due to TNK’s advantages in ease of administration and lower costs. Several studies have demonstrated at least comparable safety and efficacy profiles, culminating in TNK’s Food and Drug Administration (FDA) approval in early March 2025. Prior to this, challenges related to regulatory approvals, operational barriers, logistical constraints, and current clinical guidelines hindered the adoption of TNK across U.S. stroke systems. This mini-review seeks to address the pre-FDA approval obstacles to implementing TNK in stroke care and specifies some key aspects that support a transition, drawing insights from the early adoption experience of a U.S. health system. The discussion focuses on stakeholder involvement, formulary approval, and operational considerations, providing practical recommendations for stroke programs. The experience at Geisinger showcases a deliberate execution of a comprehensive change management strategy that resulted in successful and lasting outcomes. It may further serve as a blueprint for implementation of next generation thrombolytics yet to come.